Importance of activity and recreation for the quality of life of patients treated for cancer of the head and neck. Issue 2 (February 2019) - Rogers, S.N.; Travers, A.; Lowe, D.; Levy, A.R.; Midgely, A.W.
Abstract: The ability of patients to participate in recreational activities is an important facet of health-related quality of life (HRQoL) after treatment for cancer of the head and neck. The aim of this study was to analyse patients' responses to the activity and recreation domains of the University of Washington quality of life questionnaire (UW-QoL), and to relate them to clinical characteristics, the intensity of leisure-time exercise/week, perceived barriers that interfere with exercise, and feeling able to participate in an exercise programme. Other questionnaires used were the Godin Leisure-Time Exercise questionnaire, the Perceived Exercise Barriers questionnaire, and the Exercise Preferences questionnaire. The survey sample comprised 1021 patients of whom 437 responded (43%). Of them, 9% reported a serious problem with activity and 8% with recreation. The main influencing factors were site (oropharynx), advanced stage, radiotherapy and chemotherapy, composite flap, gastrostomy tube, and coexisting conditions. Low (worse) scores in the UW-QoL activity and recreation domains were associated with little time spent exercising, low-intensity exercise, more barriers to exercising, and a lack of preference. The use of the UW-QoL in follow-up assessments can help to identify patients who are having difficulties in these two domains, as well as those who feel able to participate in an exercise programme. Further research is required to optimise the interventions that will promote exercise and improve recovery and wellbeing.